Genetic aspects of auto-immune profiles of healthy chickens. (September 2017) - Parmentier, Henk K.; van der Vaart, Priscilla S.; Nieuwland, Mike G.B.; Savelkoul, Huub F.J.
Abstract: Auto-antibody profiles binding liver antigens differed between chicken lines divergently selected for specific antibody responses to SRBC, and were affected by ageing suggesting both genetic and environmental effects. Presence and levels of IgM and IgG antibodies binding chicken liver cell lysate (CLL) fragments in plasma at 5 weeks of age from 10 individual full sibs and their parents from 5 Hsrbc and 5 Lsrbc line families was studied to reveal genetic relations. Non-genetic maternal effects were studied by comparing auto-antibody profiles of 36 weeks old hens from 2 other unrelated lines with the profiles from their chicks at hatch. IgM and IgG antibodies from parents and progeny from both Hsrbc and Lsrbc lines bound CLL fragments. Significant line and generation differences and their interactions were found for both isotypes. Higher staining of CLL fragments was usually found for Hsrbc line birds. Lines were clustered by auto-antibody profiles, but staining by birds of both lines in both generations was very individual for IgG and IgM. The current data with full sibs therefore not supported a genetic basis for auto-antibody profiles. IgG but not IgM auto-antibody profiles of chicks correlated with maternal auto-antibody profiles. The results suggest that the auto-antibody repertoire of healthy chickens is largely stochastically initiated and may be affected by environmental challenges during ageing, but genetic mechanisms may underlie staining intensity of individual bound CLL fragments. The present results suggest that identification of fragments or profiles to be used at early age for genetic selection for health traits is not feasible yet. Secondly, the IgM profile of neonatal chickens seems non-organised independent of the maternal profile, but the neonatal IgG profile is much more related with the maternal profile. Consequences of these findings for disease susceptibility or breeding for optimal health are discussed. Highlights: Auto-antibodies binding tissue antigens are found in healthy chickens. Genetic strains of poultry differ in auto-antibody profiles, especially in the binding intensity. Auto-antibody profiles may differ between generations. Auto-antibody profiles seem stochastic of origin. Neonatal IgG antibody profiles are related with maternal antibody profiles.